The Vanishing Volcanic Geoheritage of a Key Scoria Cone and its Significance in Volcanic Hazard Resilience of the Active Monogenetic Volcanic Field near Al Madinah, Kingdom of Saudi Arabia - Karoly Nemeth; Mohammed Moufti; Mahmoud Ashor; Abdulrahman Sowaigh; Turki Hablil; Khalid Abdulhafez; Turki Sehli (Geoconservation Research)
Four small scoria cones in the western outskirts of Al Madinah City, the Kingdom of Saudi Arabia, form a distinct young volcanic landmark. These volcanoes, despite their very small size, provide one of the most fundamental sources of information about the early eruption mechanism of rising mafic magma in the context of an active volcanic field located next to a city with over one million people. An initial study of the area in 2012–2013 confirmed that these sites had a significant phreatomagmatic phase in their opening stage, leaving behind characteristic pyroclastic successions likely to be covered by subsequent eruptive products. The fact that in this location, unequivocal evidence emerged to show that explosive magma-water interaction driven eruptions occurred in the largely magmatic (“dry”) explosive style, and volcanic field evolution confirmed that this site has high geoheritage value. Since the first research was 20 years ago, a restudy of the present-day condition of the scoria cone was conducted. Applying satellite imagery, remote sensing and direct site visit, we find that about a third of the cone surface area has been modified and at least a quarter of its volume has vanished. Further excavation for cone material however opened the entire western side of the cone, exposing a nearly 5-m-thick succession of accidental lithic pyroclast-dominated lapilli tuff and tuff breccia, confirming that this location had a significant phreatomagmatic phase in its opening eruptions. This location shows graphically the need for geoconservation to preserve such sites that are potentially the only, or best locations to show the potential eruptive styles and scenarios of future eruptions if they occur in similar environments.